In vitro trypanocidal activity of extracts and compounds isolated from Vitellaria paradoxa - Guerisson Bairy; Cyrille Oliver Ozzin-Kholy Zolipou; Romaric Nzoumbou-Boko (BMC, 2023)
Abstract Background Vitellaria paradoxa is used in traditional medicine for the treatment of various diseases in tropical countries; however, nothing is known about its anti-trypanosomal activity. Human African trypanosomiasis is a neglected tropical disease of Sub-Saharan Africa's poorest rural regions, and the efficacy of its treatment remains a challenge. This study investigates the as-yet-unknown trypanocidal activity of this plant. Methods V. paradoxa, commonly known as shea tree, was selected for study based on an ethnobotanical investigation. Ultrasonicated extracts from bark and seeds were successively treated with ethyl acetate and water. Column chromatography, NMR spectroscopy and mass spectrometry were used to identify isolated compounds. Purified trypanosomes (Trypanosoma brucei brucei) were incubated with serial dilutions of the extracts and isolated compounds at 37 °C in 5% CO2 for 24 h. Parasite viability was evaluated under a microscope. Results The ethyl acetate extracts of the bark showed the higher in vitro trypanocidal activity against T. brucei brucei with median inhibitory concentration (IC50) of 3.25 µg/mL. However, the triterpene 1α,2β,3β,19α-tretrahydroxyurs-12-en-28-oic acid and the pentadecanoic acid isolated from the ethyl acetate extract of the seeds showed in vitro trypanocidal activity with IC50 of 11.30 and 70.1 µM, respectively. Conclusion The results obtained contribute to the validation of the traditional medicinal use of V. paradoxa. Our results encourage further investigations of this plant, mainly with respect to its in vivo efficacy and toxicity.